Equivalent Geometric Imperfections for Local Buckling of Slender Box-section Columns - Radwan, Mohammad; Kövesdi, Balázs (Periodica Polytechnica Civil Engineering, 2021)
Determining the plate or the local buckling resistance is highly important in designing steel buildings and bridges. The EN 1993-1-5 Annex C provides a FEM-based design approach to calculate the buckling resistance based on numerical design calculations (geometrical and material nonlinear analysis - GMNIA). Within the GMNIA analysis-based stability design, the application of the imperfections has a special role. Thus, the applicability of the EN 1993-1-5 based buckling curve (Winter curve) has been questioned for pure compression, and previous investigations showed the buckling curve of EN 1993-1-5 Annex B is more appropriate for the design of slender box-section columns subjected to pure compression, the magnitude of the equivalent geometric imperfection to be applied in numerical models for local buckling is also questioned and investigated by the authors within the current paper. The aim of the current research program is to investigate the necessary equivalent geometric imperfections to be applied in FEM-based design calculations using GMNIA calculations. A numerical parametric study is executed to investigate the imperfection sensitivity of box-section columns having different local slenderness. The necessary imperfection magnitudes are determined to each analyzed geometry leading to the buckling resistance predicted by the standardized buckling curves. Based on the numerical parametric study, a proposal for the applicable equivalent geometric imperfection magnitude is developed, which conforms to the plate buckling curves of the EN 1993-1-5 and giving an improvement proposal to the local buckling imperfection magnitudes of the prEN 1993-1-14, which is currently under development.